Machine learning with Spark : develop intelligent machine learning systems with Spark 2.x /: develop intelligent machine learning systems with Spark 2.x. (2017) - Dua, Rajdeep; Pentreath, Nick; Ghotra, Manpreet Singh
No abstract available